Induction in component-based software synthesis - Vaidas Giedrimas (Lietuvos Matematikos Rinkinys)
The automatic programming and automatic software synthesis systems are relevant software engineering research objects. This article presents the prospects of induction as a component-based software synthesis method. The usage of induction in the component-based software synthesis system can solve main synthesis problems: problem of specification, problem of undefined components and problem of non-functional requirements. However using induction synthesis system can lose soundness provided by structural synhesis of programs method. To avoid this any inductive conclusion should be verified.